Banking After Regulatory Reforms - Business as Usual? - Javier Arribas Quintana; Mattias Levin; Elleonora Soares; Jukka Vesala; Alan S. Blinder; Erkki Liikanen; Paul Tucker (SUERF - The European Money and Finance Forum, 2014)
The 5th joint SUERF/Bank of Finland joint conference was held in Helsinki on 13 June 2013. The general theme of the conference was to focus on the regulatory reforms after the global financial crisis and, in particular, how structural reforms of banking ("Volcker, Vickers and Liikanen") could still complement them. The working hypothesis for the conference was that regulatory changes are likely to affect banks' business models, and regulations on banks' structure would interfere with business models most directly. This volume comprises five chapters which are based on the key policy oriented presentations in the conference.
Keywords: G21; G28; L51; 330; bank structure; banking regulation; Liikanen report; macroprudential regulation; resolution; systemic risk; Bankenkrise; Systemrisiko; Bankenregulierung; Finanzmarktaufsicht; EU-Staaten